Communities of Care : The Social Ethics of Victorian Fiction - Schaffer, Talia, 1968- (Book collections on Project MUSE., 2016)
"Academic study about marriage and courtship in the Victorian novel. It discusses works by Jane Austen, George Eliot, Charlotte Yonge, and Margaret Oliphant, among others" --